Planar SIW diplexer using circular cavity resonator / Noor Hasimah Baba … [et al.] - Baba, Noor Hasimah; Awang, Aziati; Ali, Mohd Tarmizi; Mohd Hizan, Hizamel (Universiti Teknologi MARA, Shah Alam: Faculty of Electrical Engineering, 2017)
This paper presents a new design of planar diplexer based on substrate integrated waveguide single mode filters with circular cavity. The diplexer consists of two bandpass filters. The design is based on Substrate Integrated Waveguide (SIW) substrate fabricated by printed circuit board technique. The individual bandpass filters using the TM010 mode SIW circular resonator were designed at 2.2 GHz and 2.4 GHz. The simulation return losses for the lower and upper channels are greater than 20.94 dB and 30.92 dB respectively. The minimum insertion losses obtained are 0.87 dB and 0.74 dB at each band. The diplexer provides isolation better than 15 dB at both channels. The simulation results are in good congruent with the ideal electrical modelling response. The proposed SIW diplexer has a promising application for the uplink/downlink RF front end subsystem that is essential for wireless communications systems.